The Effectiveness of Digital Promotion in Marketing Communication to Increase The Number of Foreign Tourists in Tana Toraja Regency Post Covid-19 Pandemic - Lassa, Muhammad Amin; Sultan, M. Iqbal; Mursalim, M (Universitas Muhammadiyah Surakarta, 2023)
The diversity of tourism in Indonesia has a positive impact on the economic growth and development of the country. It was proved that tourism is the third largest foreign exchange contributor after CPO and coal. This study aims to analyze the effectiveness of digital promotion of the Tana Toraja Tourism Office to increase the number of foreign tourists in Tana Toraja Regency after the Covid-19 pandemic. The research method uses a qualitative descriptive approach with observation, in-depth interviews with sources, and documentation. Data analysis uses three steps, such as data reduction, data presentation, and conclusion. The results of the research are as follows (1) the tourism office of tana toraja district builds a tourism image after the covid pandemic through social media, especially on Instagram and TikTok. (2) Tourism branding of tana toraja district is using ayo ke toraja. Ayo ke Toraja is made as a branding to attract tourists as well as making ayo ke toraja as the name of the official social media account of the tana toraja district tourism office. (3) Digital marketing is combined with STP marketing to branding tourism in Tana Toraja district. STP Marketing consists of Segmenting, Targeting, and Positioning. The planning and implementation process consists of concept, idea, price, promotion, and distribution. STP model is a process in marketing. The implementation of the STP model in digital marketing has proved effective in attracting foreign tourists to visit the tana Toraja regency.